Water absorbing agent composition and method for producing the same

By adding polysaccharides and reducing agents to the water-absorbing resin to perform the surface cross-linking process, the problem of coloring water-absorbing resin under high temperature conditions is solved, and high quality, stability and productivity are improved. It is suitable for a variety of water-absorbing resins. Sex products.

CN115768555BActive Publication Date: 2024-12-13NIPPON SHOKUBAI CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202180047476.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-13
Filing Date
2021-07-13
Publication Date
2024-12-13
Estimated Expiration
2041-07-13

AI Technical Summary

Technical Problem

The existing water-absorbent resins are easily colored during the manufacturing process under high temperature conditions, resulting in lower physical properties and productivity problems. In particular, the compositions containing polysaccharides may have coloring problems such as tea brown during drying and surface cross-linking at high temperatures, which is difficult to inhibition.

Method used

The polyacrylic acid-based water-absorbing resin, polysaccharides and reducing agent are used to produce the polysaccharides and a reducing agent at a surface crosslinking process at a condition of 100°C or more. 10 mass% of the polysaccharides and 10 ppm to 10,000 ppm are added, and the reducing agent is used. As a reducing agent, sodium bisulfite or sodium sulfite control color (YI value) is less than 60.

Benefits of technology

A high-quality water-absorbent composition that does not color under high temperature conditions is achieved, and its colority is reduced, productivity is not reduced, and its stability is improved, and it is suitable for various water-absorbent products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004034583980000381
    Figure BDA0004034583980000381
  • Figure BDA0004034583980000391
    Figure BDA0004034583980000391
Patent Text Reader

Abstract

Provided is a water-absorbing agent composition having high quality (and stable quality) and a method for producing the same, which does not reduce productivity even when polysaccharides are used as at least a part of sustainable raw materials and does not discolor in a production process (or production conditions) under high temperature conditions (heating conditions of 100°C or more). The water-absorbing agent composition contains a polyacrylic acid (salt)-based water-absorbing resin, a polysaccharide, and a reducing agent, the surface of the water-absorbing agent composition is cross-linked, the water-absorbing agent composition contains 10% by mass or more of the polysaccharide and 10 ppm to 10,000 ppm of the reducing agent, and the coloring degree (YI value) of the water-absorbing agent composition is 60 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water absorbent composition and a method for producing the same. Background Art

[0002] Super absorbent polymer (SAP) is a water-swellable, water-insoluble cross-linked polymer that is used in diapers, sanitary napkins, adult incontinence products (incontinence pads), pet sheets and other sanitary materials (sanitary products), agricultural and horticultural soil water retention agents, industrial water stoppers and other water-absorbent items.

[0003] In recent years, biodegradable resources are preferred from the perspectives of reducing the burden on the global environment, resource conservation, carbon neutrality, and SDGs (Sustainable Development Goals). Therefore, there is a trend to actively adopt renewable organic resources (so-called sustainable raw materials) derived from animals and plants as constituent materials of native organisms, which are generally used instead of depleted energy resources such as petroleum. In addition, in the field of water-absorbent resins, research has been conducted on using polysaccharides derived from natural products as at least a part of sustainable raw materials.

[0004] For example, Non-Patent Document 1 describes that sodium starch grafted polyacrylate formed by graft polymerization of sodium acrylate and starch is sold on the market as a water-absorbent resin. Patent Documents 1 and 2 describe methods for producing the water-absorbent resin (sodium starch grafted polyacrylate).

[0005] Patent Document 4 describes a method for producing a superabsorbent composition (water-absorbent resin composition) by adding a starch compound to any step of producing a water-absorbent resin.

[0006] In addition, Patent Documents 5 and 6 also describe a method for producing a water-absorbent resin by mixing a polysaccharide such as starch into a hydrogel cross-linked polymer after polymerization of the water-absorbent resin. Patent Documents 7 to 9 propose a polyacrylic acid-based water-absorbent resin obtained by mixing cellulose as a raw material. Patent Documents 10 to 12 propose a polyacrylic acid-based water-absorbent resin obtained by mixing starch as a raw material. Patent Document 13 describes a water-absorbent resin containing a modified starch cross-linked product.

[0007] (Prior art literature)

[0008] (Patent Document)

[0009] Patent document 1: US4076663

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 54-53165

[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 1-062317

[0012] Patent Document 4: Japanese Patent Application No. 2009-528412

[0013] Patent document 5: EP0476574A2

[0014] Patent Document 6: US5340853

[0015] Patent Document 7: Japanese Patent Application Publication No. 2009-185216

[0016] Patent Document 8: Japanese Patent Application Publication No. 2009-242466

[0017] Patent Document 9: Japanese Patent Application Publication No. 2012-031217

[0018] Patent Document 10: Japanese Patent Application Publication No. H07-228640

[0019] Patent Document 11: Japanese Patent Application Publication No. 2013-034942

[0020] Patent Document 12: Japanese Patent Application Publication No. 2011-213759

[0021] Patent Document 13: Japanese Patent Application Publication No. 2013-253262

[0022] Patent Document 14: WO2011 / 126079

[0023] Patent Document 15: WO2016 / 158975

[0024] Patent Document 16: WO2016 / 204302

[0025] Patent Document 17: Japanese Patent Application Publication No. 2001-79829

[0026] Patent Document 18: Japanese Patent Application Laid-Open No. 63-118375

[0027] Patent Document 19: Japanese Patent Application Publication No. 2004-210924

[0028] Patent Document 20: Japanese Patent Application Publication No. 2003-206305

[0029] Patent Document 21: Japanese Patent Application Publication No. 2005-29751 (Non-Patent Document)

[0030] Non-patent document 1: Japanese Pharmacopoeia (1989) pp. 1319-1320 Summary of the invention

[0031] (Problems to be solved by the invention)

[0032] The water-absorbent resin itself is originally white, but since the water-absorbent resin is mixed with white pulp when it is mainly used in diapers and sanitary napkins, it is generally undesirable to color the water-absorbent resin from the perspective of hygienic appearance. However, the polysaccharides represented by starch used in the above-mentioned patent documents 1 to 13 generally lack heat resistance. Therefore, the water-absorbent composition obtained by adding polysaccharides to monomers or water-absorbent resins during the manufacturing process has the problem of coloring such as brown due to the high temperature conditions process in the manufacturing process (for example, the high temperature drying process of the water-containing water-absorbent resin (water-containing gel-like cross-linked polymer) or the high temperature surface cross-linking process). In addition, if it is difficult to perform drying treatment at high temperature and surface cross-linking treatment at high temperature, and drying is performed at low temperature to suppress the above coloring, the problem of reduced physical properties and productivity of the water-absorbent composition occurs. That is, if the water-absorbent composition containing polysaccharides is placed under high temperature conditions (heating conditions above 100°C) during its manufacturing process, it will be colored. In order to suppress this coloring, the manufacturing process (or manufacturing conditions) will be restricted. In order to improve the physical properties of the water-absorbent resin, surface crosslinking is also performed after drying. However, due to the limitations of the above-mentioned production conditions (drying conditions and surface crosslinking conditions), the physical properties of the water-absorbent resin containing polysaccharides are usually low or the price is expensive.

[0033] Therefore, there is a need for a high-quality (and stable-quality) water-absorbing agent composition and a method for producing the same, which does not reduce productivity even when polysaccharides are used as at least a part of sustainable raw materials and does not discolor in a production process (or production conditions) under high-temperature conditions (heating conditions of 100° C. or more).

[0034] That is, a main object of one aspect of the present invention is to provide a high-quality (and stable-quality) water-absorbing agent composition and a method for producing the same, which does not reduce productivity and does not cause coloring during heating in the production process, i.e., does not cause coloring in the production process (or production conditions) under high temperature conditions (heating conditions of 100° C. or more), even if polysaccharides are used as at least a part of the sustainable raw materials.

[0035] (Methods used to solve problems)

[0036] The present inventors have conducted various studies to solve the above-mentioned problems, and as a result, found that a reducing agent can effectively prevent the coloring of polysaccharides (especially starch) mixed with a water-absorbing resin (especially a hydrogel-like cross-linked polymer) when heated at high temperatures, thereby completing the present invention. That is, it was found that the above-mentioned problems can be solved by the following water-absorbing agent composition, thereby completing the present invention. The water-absorbing agent composition contains a polyacrylic acid (salt)-based water-absorbing resin, a polysaccharide and a reducing agent, the water-absorbing agent composition has been surface cross-linked, the water-absorbing agent composition contains 10% by mass or more of the polysaccharide and 10 ppm to 10000 ppm of the reducing agent, and the coloring degree (YI value) of the water-absorbing agent composition is 60 or less.

[0037] That is, the present invention includes the inventions described in the following [1] to

[11] .

[0038] [1] A water-absorbing agent composition comprising a polyacrylic acid (salt)-based water-absorbing resin, a polysaccharide and a reducing agent, wherein the water-absorbing agent composition is surface cross-linked, contains 10% by mass or more of the polysaccharide and 10 ppm to 10,000 ppm of the reducing agent, and has a coloring degree (YI value) of 60 or less.

[0039] [2] The water-absorbing agent composition according to [1], wherein the reducing agent contains one or more compounds selected from the group consisting of an inorganic compound containing a sulfur atom, an organic compound containing a sulfur atom, and an inorganic compound containing a phosphorus atom.

[0040] [3] The water absorbing agent composition according to [1] or [2], wherein the reducing agent is sodium bisulfite and / or sodium sulfite.

[0041] [4] The water absorbing agent composition according to any one of [1] to [3], wherein the polysaccharide is starch and / or a modified starch.

[0042] [5] The water absorbing agent composition according to any one of [1] to [4], wherein the residual monomer content in the water absorbing agent composition is 1000 ppm or less.

[0043] [6] The water absorbing agent composition according to any one of [1] to [5], which has an absorption under pressure (AAP0.3) of 10 g / g or more at a pressure of 0.3 kPa.

[0044] [7] A method for producing a water-absorbing agent composition, wherein the water-absorbing agent composition contains a polyacrylic acid (salt)-based water-absorbing resin, a polysaccharide and a reducing agent, the method comprising: as the steps for producing the water-absorbing agent composition, a polymerization step, a drying step and a surface cross-linking step are sequentially included, and at any stage between the start of the polymerization step and the end of the surface cross-linking step, 10% by mass or more of the polysaccharide and 10 ppm to 100,000 ppm of the reducing agent are added relative to the total mass of the monomer composition and the polysaccharide introduced into the polymerization step.

[0045] [8] The method for producing a water-absorbing agent composition according to [7], wherein the polysaccharide is added after the polymerization step is completed.

[0046] [9] The method for producing a water absorbent composition according to [7] or [8], further comprising a gel grinding step between the polymerization step and the drying step, wherein the polysaccharide is added at at least one of the following stages: after the polymerization step is completed and before the gel grinding step is started, at the start of the gel grinding step, and during the gel grinding step.

[0047]

[10] The method for producing a water absorbing agent composition according to any one of [7] to [9], wherein the reducing agent is added during the period from the completion of the polymerization step to the start of the drying step.

[0048]

[11] The method for producing a water-absorbing agent composition according to any one of [7] to [9], further comprising a gel grinding step between the polymerization step and the drying step, wherein the reducing agent is added during the period from before the gel grinding step starts after the polymerization step to before the surface cross-linking step starts.

[0049]

[12] The method for producing a water-absorbing agent composition according to [7] to

[11] , further comprising a gel grinding step between the polymerization step and the drying step, wherein the reducing agent is added after the polymerization step and before the gel grinding step is started, and / or at the start of the gel grinding step.

[0050]

[13] The method for producing a water-absorbing agent composition according to [7], further comprising a gel crushing step between the polymerization step and the drying step, wherein the polysaccharide is added at least one of the following stages: after the polymerization step is completed and before the gel crushing step is started, at the start of the gel crushing step, and during the gel crushing step, and the reducing agent is added during the period from before the start of the gel crushing step after the polymerization step is completed to before the start of the surface cross-linking step.

[0051]

[14] The method for producing a water absorbing agent composition according to any one of [7] to

[13] , wherein the surface cross-linking step includes a surface cross-linking reaction at 100 to 250°C.

[0052]

[15] A water absorbing agent composition produced by the method for producing a water absorbing agent composition according to any one of [7] to

[14] .

[0053] In addition, the present invention also includes the following inventions.

[0054]

[16] The method for producing a water-absorbing agent composition according to any one of [7] to

[14] , further comprising a gel grinding step between the polymerization step and the drying step, wherein the hydrogel-like cross-linked polymer obtained in the polymerization step is gel-ground in such a manner that the mass average particle size d1 of the hydrogel-like cross-linked polymer is 1 mm or less, wherein the mass average particle size d1 is calculated based on the solid content of the hydrogel-like cross-linked polymer.

[0055]

[17] The method for producing a water absorbing agent composition according to any one of [7] to

[14] and

[16] , wherein the polysaccharide is starch and / or a modified starch.

[0056]

[18] The method for producing a water-absorbing agent composition according to

[17] , wherein the particle size of the starch and / or modified starch is 1 to 1000 μm.

[0057] (Effects of the Invention)

[0058] According to one aspect of the present invention, the following effects are achieved: even if a polysaccharide is used as at least a part of the sustainable raw material, the productivity is not reduced and the coloring is not caused by heating during the production process, that is, the high-quality (and stable quality) water-absorbing agent composition and the production method thereof are provided, which are not colored in the production process (or production conditions) under high temperature conditions (heating conditions of 100° C. or more) DETAILED DESCRIPTION

[0059] The following is a detailed description of the embodiments of the present invention. However, the present invention is not limited thereto, and various changes can be made within the scope described above. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. Unless otherwise specified in this specification, "A to B" indicating a numerical range means "Above A and Below B", and "ppm" means "mass ppm" or "weight ppm". In addition, "(meth)propylene" means "propylene and / or methpropylene", and "mass" and "weight" are considered synonymous. In addition, regarding the mass of a water-absorbent resin, a water-absorbent resin composition, and a water-absorbing agent composition, unless otherwise specified, the numerical value refers to the solid content conversion amount thereof.

[0060] [1] Definition of terms

[0061] [1-1] Water-absorbent resin, water-absorbent resin composition, water-absorbent composition In the present specification, the water-absorbent resin refers to a water-swellable, water-insoluble cross-linked polymer, generally in the form of particles. Water-swellability means that the water absorption capacity under no pressure (CRC) specified in NWSP 241.0.R2 (15) is 5 g / g or more, and water-insolubility means that the amount of soluble components (Ext) specified in NWSP 270.0.R2 (15) is 50% by mass or less.

[0062] The water-absorbent resin is a hydrophilic cross-linked polymer obtained by cross-linking and polymerizing an unsaturated monomer having a carboxyl group.

[0063] In this specification, the water-absorbent resin may refer to a "polymer cross-linked only internally", i.e., a polymer having substantially the same cross-linking density internally and on the surface; or a "polymer cross-linked both internally and on the surface", i.e., a polymer having a relatively higher cross-linking density on the surface than on the internal cross-linking density.

[0064] In this specification, the "polymer cross-linked only internally" and the "polymer cross-linked both internally and on the surface" are both referred to as "water-absorbent resin". However, if it is necessary to clearly distinguish whether or not surface cross-linking is present, the "polymer cross-linked only internally" is referred to as "water-absorbent resin before surface cross-linking" or "base polymer" because it is a polymer before surface cross-linking is performed, and the "polymer cross-linked both internally and on the surface", i.e., a polymer having a relatively high surface cross-linking density relative to the internal cross-linking density, is referred to as "water-absorbent resin after surface cross-linking" or "surface cross-linked water-absorbent resin" because it is a polymer after surface cross-linking is performed. In addition, "before surface cross-linking" means "before adding a surface cross-linking agent" or "before the surface cross-linking reaction under heat treatment has not started even though a surface cross-linking agent has been added".

[0065] In this specification, "water-absorbent resin" refers to only the resin component. If it contains components other than the resin such as additives, it is referred to as a "water-absorbent resin composition". If the water-absorbent resin that has not been surface-crosslinked contains additives, it is referred to as a "water-absorbent resin composition before surface crosslinking" or a "base polymer composition". If the water-absorbent resin that has been surface-crosslinked contains additives, it is referred to as a "water-absorbent resin composition after surface crosslinking" or a "water-absorbent resin composition that has been surface-crosslinked".

[0066] In addition, in this specification, the "water-absorbent resin composition" in a state ready for shipment as a final product is particularly referred to as a "water-absorbing agent composition".

[0067] [1-2] Acrylic acid (salt) monomer composition, polyacrylic acid (salt) water-absorbent resin In the present specification, acrylic acid (salt) refers to acrylic acid and / or its salts. Acrylic acid (salt) monomer composition refers to a monomer composition containing 50 mol% or more of acrylic acid (salt) based on the total amount of monomers excluding the internal crosslinking agent.

[0068] In this specification, the polyacrylic acid (salt) water-absorbing resin refers to a cross-linked polymer obtained by using the acrylic acid (salt) monomer composition as a raw material. That is, it refers to a cross-linked polymer containing 50 mol% or more of a structural unit derived from acrylic acid (salt) relative to the total amount of structural units constituting the polyacrylic acid (salt) water-absorbing resin, and containing a graft component as an optional component.

[0069] Specifically, the polyacrylic acid (salt)-based water-absorbing resin refers to a polymer obtained by using acrylic acid (salt) as a raw material in an amount of preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more and preferably 100 mol% or less, particularly preferably substantially 100 mol% relative to the portion of the monomer components participating in the polymerization reaction excluding the internal crosslinking agent.

[0070] The water-absorbing resin composition or water-absorbing agent composition containing a polyacrylic acid (salt)-based water-absorbing resin as a main component refers to a composition containing 50% by mass or more of the polyacrylic acid (salt)-based water-absorbing resin.

[0071] 〔1-3〕NWSP

[0072] NWSP is the abbreviation of Non-Woven Standard Procedures-Edition 2015, which is an evaluation method for nonwoven fabrics and their products jointly developed by EDANA (European Disposables and Nonwovens Associations) and INDA (Association of the Nonwoven Fabrics Industry) and uniformly adopted in Europe and the United States. In addition, NWSP also shows a standard measurement method for water-absorbent resins. This manual measures the physical properties of water-absorbent resins (water-absorbent resin compositions or water-absorbing agent compositions) in accordance with the original NWSP (2015).

[0073] Unless otherwise specified in the present specification, the measurement of various physical properties of the water-absorbent resin, the water-absorbent resin composition or the water-absorbing agent composition shall be carried out according to the measurement methods of the following Examples.

[0074] [2] Water-absorbing agent composition

[0075] A water absorbing agent composition according to one embodiment of the present invention is a water absorbing agent composition comprising a polyacrylic acid (salt)-based water absorbing resin, a polysaccharide, and a reducing agent, wherein the water absorbing agent composition is surface cross-linked, the water absorbing agent composition contains 10% by mass or more of the polysaccharide and 10 to 10000 ppm of the reducing agent, and the coloring degree (YI value) of the water absorbing agent composition is 60 or less.

[0076] The water absorbent composition is obtained by surface crosslinking in a state where a polyacrylic acid (salt) water absorbent resin and a polysaccharide are mixed and / or kneaded (a state where the water absorbent resin and the polysaccharide are mixed and integrated). It is preferred that the surface crosslinking is performed in a state where the water absorbent resin and the polysaccharide are mixed and integrated. For example, there can be mentioned: a composite resin obtained by uniformly kneading a polysaccharide and a polyacrylic acid (salt) water absorbent resin; and a surface crosslinked polyacrylic acid (salt)-polysaccharide complex obtained by polymerizing an acrylic acid (salt) monomer and an internal crosslinking agent as raw materials in the presence of a polysaccharide. The water absorbent composition may contain independently existing polyacrylic acid (salt) water absorbent resins and / or polysaccharides. The polysaccharide exposed on the surface of the composite resin may also be a non-surface crosslinked portion.

[0077] [Polyacrylic acid (salt) water-absorbent resin]

[0078] The polyacrylic acid (salt)-based water-absorbing resin (hereinafter referred to as "water-absorbing resin") is a cross-linked polymer obtained by polymerizing a monomer composition containing an acrylic acid (salt)-based monomer as a main component in the presence of a polymerization initiator.

[0079] (a) Monomer

[0080] The monomer is a raw material component (monomer) for forming a water-absorbent resin (polymer), and includes an acrylic acid (salt) monomer, a monomer other than the acrylic acid (salt) monomer, and an internal crosslinking agent. All monomers for forming a water-absorbent resin, i.e., a monomer composition. Examples of acrylic acid (salt) monomers include (meth)acrylic acid and its salts.

[0081] As monomers other than acrylic acid (salt) monomers that may be contained in the monomer composition, monomers containing acid groups among the monomers having unsaturated double bonds (ethylenically unsaturated monomers) are preferred. As such monomers, specifically, maleic acid (anhydride), fumaric acid, crotonic acid, itaconic acid, 2-(methyl)acryloylethanesulfonic acid, 2-(methyl)acryloylpropanesulfonic acid, 2-(methyl)acrylamide-2-methylpropanesulfonic acid, vinylsulfonic acid, styrenesulfonic acid, and salts thereof may be cited. One or more of these monomers may be used as required.

[0082] Examples of the salt include alkali metal salts, ammonium salts, and amine salts, and sodium salts, potassium salts, lithium salts, and ammonium salts are more preferred, and sodium salts are particularly preferred.

[0083] The monomer composition containing acrylic acid (salt) monomers as the main component is preferably neutralized in the range of 10 to 90 mol %, more preferably in the range of 40 to 80 mol %, and particularly preferably in the range of 60 to 75 mol %.

[0084] Therefore, the monomer composition containing acrylic acid (salt) monomer as the main component is preferably neutralized by a neutralizing solution containing the following monovalent alkaline compounds: alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide; carbonates (hydrogen) such as sodium (hydrogen) carbonate and potassium (hydrogen) carbonate; ammonia, etc. It is particularly preferred to be neutralized by a neutralizing solution containing sodium hydroxide.

[0085] In addition, the monomer composition may be neutralized after the completion of the polymerization. That is, the hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") may be neutralized to obtain a neutralized product. However, considering the productivity and various physical properties of the water-absorbent resin, it is more preferable to use a neutralized monomer composition for polymerization to obtain a hydrogel.

[0086] In addition, as required, the monomer composition may contain hydrophilic or hydrophobic unsaturated monomers (hereinafter referred to as "other monomers") in addition to the above-mentioned monomers. Examples of such other monomers include N-vinyl-2-pyrrolidone, N-vinylacetamide, (meth)acrylamide, N-isopropyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, 2-hydroxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, stearyl acrylate, and the like. The amount of other monomers used may be such that the physical properties of the obtained water-absorbing agent composition are not affected. Specifically, the amount of other monomers used is 50 mol% or less, and more preferably 20 mol% or less, relative to the portion of the monomer composition other than the internal crosslinking agent.

[0087] (b) Internal crosslinking agent

[0088] As the internal crosslinking agent, for example, there can be mentioned: a compound having at least two polymerizable double bonds in the molecule, such as N,N'-methylenebisacrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, (polyoxyethylene) trimethylolpropane tri(meth)acrylate, trimethylolpropane di(meth)acrylate, polyethylene glycol di(β-acryloxypropionate), trimethylolpropane tri(β-acryloxypropionate), poly(meth)allyloxyalkane, etc.; a compound that can react with a carboxyl group to form a covalent bond, such as polyglycidyl ether (ethylene glycol diglycidyl ether, etc.), polyol (ethylene glycol, polyethylene glycol, glycerol, sorbitol, etc.), etc. More preferably, a compound having at least two polymerizable double bonds in the molecule. These internal crosslinking agents can be used alone or in combination as needed.

[0089] In consideration of the physical properties of the obtained water-absorbing agent composition, the internal crosslinking agent is preferably used in an amount of 5.0 mol% or less, more preferably 2.0 mol% or less, further preferably 0.5 mol% or less, particularly preferably 0.1 mol% or less, and most preferably 0.01 to 0.1 mol% or less, relative to the total amount of monomers excluding the internal crosslinking agent in the monomer composition. In addition, the crosslinking method using the internal crosslinking agent can be used in combination with a known crosslinking method such as free radical self-crosslinking during polymerization and radiation crosslinking.

[0090] (c) Polymerization initiator

[0091] As the polymerization initiator, for example, photodecomposition type polymerization initiator, thermal decomposition type polymerization initiator, redox type polymerization initiator, etc. can be cited. The amount of the polymerization initiator used is preferably in the range of 0.0001 to 1 mol %, and more preferably in the range of 0.0005 to 0.5 mol % relative to the total amount of monomers in the monomer composition excluding the internal crosslinking agent. As the photodecomposition type polymerization initiator, for example, benzoin derivatives, benzyl derivatives, acetophenone derivatives, dibenzophenone derivatives, azo compounds, etc. can be cited. As the thermal decomposition type polymerization initiator, for example, persulfates (sodium persulfate, potassium persulfate, ammonium persulfate), peroxides (hydrogen peroxide, tert-butyl peroxide, methyl ethyl ketone peroxide), azo compounds (2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, etc.) can be cited. As the redox polymerization initiator, for example, there can be mentioned an initiator obtained by combining the above-mentioned persulfate or peroxide (oxidant) with a reducing compound (reducing agent) such as L-ascorbic acid or sodium bisulfite. In addition, when using a redox polymerization initiator, it is more preferable to combine the redox polymerization initiator with a persulfate, so that the amount of unreacted monomers (residual monomers) contained in the final product water-absorbing agent composition obtained through the polymerization step can be reduced.

[0092] In addition, it is also a preferred embodiment to use a photodegradable polymerization initiator and a thermal degradable polymerization initiator in combination. The ratio (molar ratio) of the combination in this case can be appropriately set, and is preferably 1 / 100 to 100 / 1, and more preferably 1 / 10 to 10 / 1.

[0093] Furthermore, since the persulfate and peroxide used as the polymerization initiator are consumed during the polymerization of the monomer composition, they do not remain in the obtained water absorbing agent composition.

[0094] Furthermore, polymerization can be carried out using active energy rays such as ultraviolet rays, with or without using a polymerization initiator.

[0095] (d) Solvent

[0096] The solvent used in the polymerization of the monomer composition is not particularly limited. That is, a known solvent can be appropriately used in the polymerization of the monomer composition. As the known solvent, deionized water (ion exchange water) is preferred, and the monomer composition obtained using the deionized water (ion exchange water) is particularly referred to as a monomer aqueous solution.

[0097] 〔Polysaccharides〕

[0098] As polysaccharides that can be used in the present invention, for example, natural polysaccharides or modified products thereof obtained from organisms can be cited. These polysaccharides do not use fossil raw materials such as petroleum, so they can be said to be renewable raw materials. The polysaccharides are polymers with a skeleton containing monosaccharide repeating units. As polysaccharides, for example, starch, amylopectin, amylose, galactomannan, glucomannan, xanthan gum, carrageenan, chitin, chitosan, and their modified products can be cited. As starch, for example, corn starch, potato starch, wheat starch, cassava starch, glutinous corn starch, rice starch, sweet potato starch, etc. can be cited. As cellulose, for example, cotton, pulp derived from wood, bacterial cellulose, wood cellulose, regenerated cellulose (cellophane, regenerated fiber, etc.), microcrystalline cellulose, etc. can be cited. As galactomannan, for example, guar gum, locust bean gum, tara gum, cassia gum, etc. can be cited.

[0099] In addition, regarding the modification methods for obtaining modified starch, modified amylopectin, modified amylose, modified cellulose, modified galactomannan, modified glucomannan, modified xanthan gum, modified carrageenan, etc., esterification such as acetylation, etherification such as carboxyl alkylation, phosphorylation, oxidation, sulfation, phosphoric acid crosslinking, adipic acid crosslinking, enzyme treatment, and combinations thereof can be cited. The type of substituent introduced by modification can be one or two. Considering the physical properties of the water-absorbing agent composition to be obtained, the degree of substitution during modification is preferably 2 or less, more preferably 1 or less, further preferably 0.5 or less, and particularly preferably 0.25 or less.

[0100] In addition, polysaccharides can be cross-linked. Polysaccharides can be cross-linked by any known method, specifically, a cross-linking agent can be used for cross-linking, or by radiation (for example, radiation such as gamma rays, X-rays, electron beams) and / or heat for cross-linking. As the cross-linking agent, for example, N-methylol compounds (dimethylol ethylene urea, dimethylol dihydroxy ethylene urea, etc.), polycarboxylic acids (citric acid, propane tricarboxylic acid, butane tetracarboxylic acid, etc.) with a cyclic portion in the molecule can be cited, multifunctional epoxy compounds (ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, glycerol diglycidyl ether, etc.), polyvalent metal ions (aluminum ions, chromium ions, etc.), multifunctional amines (amino acids, polyamines, triamines, diamines, etc.), multifunctional aldehydes (glutaraldehyde, glyoxal, etc.), etc. These cross-linking agents can be used one or more than two as needed.

[0101] Among the polysaccharides, starch, cellulose, and their modified products are more preferred in terms of availability, unmodified starch and unmodified cellulose are further preferred, and unmodified starch is most preferred. Starch, in particular, can be made fluid by gelatinization (alpha-modification), so that it can be uniformly mixed into the water-absorbent resin. This can prevent the polysaccharide from being concentrated in one place in the water-absorbent resin composition (only the polysaccharide is present in large quantities), so it is most preferred.

[0102] These polysaccharides can be used alone or in combination as required. The particle size of the polysaccharide is preferably in the range of 1 μm to 1000 μm, more preferably in the range of 1 μm to 500 μm, and further preferably in the range of 1 μm to 200 μm. In addition, if the polysaccharide is starch, its particle size is preferably in the range of 1 μm to 150 μm, and more preferably in the range of 1 μm to 100 μm.

[0103] The molecular weight of the polysaccharide is preferably 500 or more, more preferably 1000 or more, further preferably 2000 or more, particularly preferably 5000 or more, and most preferably 10000 or more. The upper limit of the molecular weight of the polysaccharide is not particularly limited, but is preferably 10 million or less, more preferably 8 million or less, and further preferably 5 million or less. If the molecular weight of the polysaccharide is less than 500, the water absorption rate of the water absorbent composition may be low. In addition, if the molecular weight of the polysaccharide exceeds 10 million, it is difficult to handle.

[0104] Taking the total amount of the water-absorbing agent composition as 100% by mass, the amount of polysaccharides contained in the water-absorbing agent composition is preferably 10% by mass or more, and more preferably 20% by mass or more. The upper limit of the content of polysaccharides is preferably 50% by mass or less, and more preferably 30% by mass or less. Therefore, in order to make the amount of polysaccharides contained in the obtained water-absorbing agent composition the above amount, as described later, polysaccharides are preferably added to the water-containing gel in the water-absorbing resin. If the content of polysaccharides is less than 10% by mass, the amount of polysaccharides used as a sustainable raw material is less. If the content of polysaccharides exceeds 50% by mass, the water absorption rate of the water-absorbing agent composition may be low.

[0105] 〔reducing agent〕

[0106] The reducing agent contains one or more selected from the following: an inorganic compound containing a sulfur atom, an organic compound containing a sulfur atom, and an inorganic compound containing a phosphorus atom. Examples of the inorganic compound containing a sulfur atom include sulfites (sodium sulfite, potassium sulfite, ammonium sulfite, etc.), bisulfites (sodium bisulfite, potassium bisulfite, ammonium bisulfite, etc.), ferrous salts (ferrous sulfate, etc.), cuprous salts (cuprous sulfate, etc.), etc. Examples of the organic compound containing a sulfur atom include 2-hydroxy-2-sulfonic acid acetic acid and its salts, 2-hydroxy-2-sulfinic acid acetic acid and its salts, etc. Examples of the inorganic compound containing a phosphorus atom include phosphorous acid and phosphites (disodium phosphite, dipotassium phosphite, diammonium phosphite, etc.), hydrogen phosphites (sodium hydrogen phosphite, potassium hydrogen phosphite, ammonium hydrogen phosphite, etc.), hypophosphorous acid and hypophosphites (sodium hypophosphite, potassium hypophosphite, ammonium hypophosphite, etc.). One or more of these reducing agents can be used as needed. Among the reducing agents, reducing agents containing an inorganic compound containing a sulfur atom are preferred, and sodium hydrogen sulfite and sodium sulfite are more preferred.

[0107] The amount of the reducing agent contained in the water absorbing agent composition is preferably in the range of 10 to 10000 ppm, more preferably in the range of 30 to 5000 ppm, and further preferably in the range of 50 to 3000 ppm relative to the total amount of the water absorbing agent composition. Therefore, in order to make the amount of the reducing agent contained in the obtained water absorbing agent composition the above amount, as described later, the reducing agent is added to the water-absorbing resin, preferably to the hydrogel. If the content of the reducing agent is lower than the above range, the heating during the manufacturing process may cause the water absorbing agent composition to be colored. If the content of the reducing agent is higher than the above range, the various physical properties (water absorption properties) of the water absorbing agent composition may be reduced.

[0108] 〔Optional ingredients〕

[0109] The water-absorbing agent composition may further contain the following optional components: water-soluble resins or water-absorbing resins such as polyvinyl alcohol and polyethyleneimine; thermoplastic resins such as polyethylene and polypropylene; foaming agents (carbonates, azo compounds, bubbles, etc.); surfactants; additives (deodorants, antibacterial agents, fragrances; inorganic powders such as silicon dioxide and titanium oxide; pigments, dyes, hydrophilic short fibers, plasticizers); chelating agents such as diethylenetriamine 5-acetic acid 3-sodium (DTPA 3Na), hydroxycarboxylic acids. Regarding the amount of these optional components added, if the optional components are the water-soluble resins, water-absorbing resins, and thermoplastic resins, then the amount is preferably 50% by mass or less, more preferably 20% by mass or less, particularly preferably 10% by mass or less, and most preferably 3% by mass or less, relative to the total amount of monomers in the monomer composition excluding the internal crosslinking agent. In addition, if the optional components are the foaming agents, surfactants, and additives, then the amount is preferably 5% by mass or less, and more preferably 1% by mass or less. In the case of the chelating agent or hydroxycarboxylic acid, the concentration is preferably in the range of 10 to 5000 ppm, more preferably in the range of 10 to 1000 ppm, further preferably in the range of 50 to 1000 ppm, and particularly preferably in the range of 100 to 1000 ppm.

[0110] According to the water absorbent composition of one embodiment of the present invention, it is possible to suppress "coloration caused by heating during the manufacturing process" which exists in conventional water absorbent compositions containing polysaccharides. It should be noted that the mechanism of suppressing "coloration caused by heating during the manufacturing process" is very different from the problem to be solved by the above-mentioned Patent Documents 7 to 9, "preventing the water absorbent resin composition containing no polysaccharides from coloring over time". Specifically, the "coloration caused by heating during the manufacturing process" existing in the water absorbent composition containing polysaccharides refers to, for example, the coloration caused by the surface crosslinking process at 150°C or above of the base polymer composition containing polysaccharides (starch) and polyacrylic acid (salt)-based water absorbent resin (i.e., the coloration immediately after the manufacturing process is completed), while in contrast, the "coloration over time" existing in the water absorbent composition containing no polysaccharides refers to, for example, the coloration generated after being left for one week under the conditions of 90°C and 90%RH (i.e., the coloration generated during the storage period after manufacturing), and the two are different colors.

[0111] [3] Method for producing water-absorbing agent composition

[0112] A method for producing a water-absorbent resin composition according to one embodiment of the present invention is a method for producing a water-absorbent composition containing a polyacrylic acid (salt)-based water-absorbent resin, a polysaccharide, and a reducing agent, wherein as the steps for producing the water-absorbent composition, a polymerization step, a drying step, and a surface cross-linking step are included in this order, and at any stage during the period from the start of the polymerization step to the end of the surface cross-linking step, 10% by mass or more of the polysaccharide and 10 ppm to 100,000 ppm of the reducing agent are added relative to the total mass of the monomer composition and the polysaccharide introduced into the polymerization step.

[0113] 〔Polymerization process〕

[0114] The polymerization method of the monomer composition is not particularly limited, and the known reverse suspension polymerization method or aqueous solution polymerization method can be used. The reverse suspension polymerization method is a polymerization method in which an aqueous solution of the monomer composition (hereinafter referred to as "monomer aqueous solution") is suspended in a hydrophobic organic solvent (dispersion medium) and polymerized. The aqueous solution polymerization method is a polymerization method in which an aqueous monomer solution is polymerized without using a dispersion solvent. Among the above-mentioned polymerization methods, the aqueous solution polymerization method is preferred in consideration of productivity, ease of polymerization control, various physical properties of the obtained water-absorbing resin, etc. Through these polymerizations, a cross-linked polymer (hydrogel) containing water can be obtained.

[0115] Examples of the aqueous solution polymerization method include a stationary polymerization method in which an aqueous monomer solution is polymerized in a stationary state and a stirring polymerization method in which polymerization is performed in a stirring device.

[0116] Among the static polymerization methods, a continuous static polymerization method using a circulating belt or a polymerization container is more preferred. As the circulating belt, a resin or even rubber belt is preferred, from which the polymerization heat is difficult to escape from the contact material surface. In addition, the polymerization container preferably has an open space at its upper part.

[0117] When the circulating belt is used, the amount of the monomer aqueous solution supplied is usually preferably such that the depth of the monomer aqueous solution on the circulating belt is in the range of 1 to 100 mm, more preferably in the range of 3 to 50 mm, and further preferably in the range of 5 to 30 mm. If the depth of the aqueous solution is less than 1 mm, it may be difficult to adjust the temperature of the monomer aqueous solution. On the other hand, if the depth of the monomer aqueous solution exceeds 100 mm, it may be difficult to remove the polymerization heat.

[0118] In the stirring polymerization method, a single-shaft stirrer or a stirrer with two or more shafts is used appropriately. As the stirring polymerization method, continuous kneader polymerization is preferred.

[0119] In one embodiment of the present invention, the concentration of the active ingredient (the total of the monomer composition, the polymerization initiator, and the optional components) in the aqueous monomer solution is not particularly limited, but is preferably in the range of 30 to 80% by mass, more preferably in the range of 40 to 70% by mass, and still more preferably in the range of 45 to 65% by mass. If the concentration of the active ingredient is less than 30% by mass, the productivity of the water absorbing agent composition may be low, and if it exceeds 70% by mass, the water absorption rate of the water absorbing agent composition may be low.

[0120] When preparing the aqueous monomer solution, the neutralization of the monomer is preferably performed in an adiabatic state. In addition, it is more preferable to continuously perform polymerization while continuously neutralizing the monomer. In this way, the generated neutralization heat and / or hydration heat can be effectively used to increase the temperature of the aqueous monomer solution.

[0121] In addition, the generated heat of neutralization and / or heat of hydration can also be preferably used to remove dissolved oxygen from the monomer aqueous solution. By utilizing the heat of neutralization and / or heat of hydration, there is no need to blow an inert gas into the monomer aqueous solution or perform decompression degassing to volatilize and remove the dissolved oxygen that hinders polymerization. Specifically, the monomer aqueous solution is heated by the heat of neutralization and / or heat of hydration to make the amount of dissolved oxygen in the monomer aqueous solution preferably less than 4 mg / L, more preferably less than 2 mg / L, and even more preferably less than 1 mg / L. The prepared monomer aqueous solution is preferably gently stirred in an inert gas (preferably nitrogen) atmosphere in a manner that does not allow bubbles to mix in.

[0122] In addition, it is preferred that part or all of the monomer composition, neutralizing solution, deionized water (ion exchange water), etc. be deoxygenated before preparing the monomer aqueous solution, and dissolved oxygen be further removed by neutralization heat and / or hydration heat when preparing the monomer aqueous solution. However, if the polymerization initiator is also line-mixed with the monomer composition and the neutralizing solution, and polymerization is started at a temperature of 80° C. or above, it is preferred to reduce the amount of deoxygenation of the monomer composition, neutralizing solution, deionized water (ion exchange water), etc., or not to perform deoxygenation in order to prevent polymerization from starting during the line mixing process.

[0123] In consideration of ease of handling, etc., the polymerization is usually carried out under normal pressure, but it is preferred to carry out the polymerization under reduced pressure while removing water in order to lower the boiling temperature of the aqueous monomer solution.

[0124] The polymerization start temperature is not particularly limited, but is generally preferably in the range of 20 to 105°C, more preferably in the range of 50 to 100°C, further preferably in the range of 60 to 100°C, and most preferably in the range of 70 to 100°C. If the polymerization start temperature is lower than 20°C, the polymerization time is long, and the productivity and / or various physical properties of the water absorbent composition may be low. If the polymerization start temperature exceeds 105°C, although the productivity can be improved, since the preparation time (the time from when the polymerization start conditions are met to when the polymerization actually starts) is short, it may be difficult to control the polymerization when performing the mixing operation of the polymerization initiator, etc. In order to make the polymerization start temperature above 50°C, the polymerization device and / or the monomer aqueous solution may be heated, but it is preferred to use the above-mentioned neutralization heat and / or hydration heat.

[0125] The polymerization start temperature can be measured by observing the turbidity, viscosity increase, temperature increase, etc. of the monomer aqueous solution. In addition, when polymerization is carried out using active energy rays such as ultraviolet rays, a redox polymerization initiator, or an azo compound, the preparation time is generally short, about 1 second to 1 minute, so the polymerization start temperature can be specified by the temperature of the monomer aqueous solution just before the addition of the polymerization initiator or just before the irradiation of the active energy ray.

[0126] The maximum temperature (peak temperature) during polymerization is not particularly limited, but is preferably in the range of 60 to 150°C, more preferably in the range of 70 to 140°C, further preferably in the range of 80 to 130°C, particularly preferably in the range of 85 to 120°C, and most preferably in the range of 90 to 115°C. If the maximum temperature exceeds 150°C, the various physical properties of the obtained water-absorbing agent composition may be low. After the start of polymerization, the temperature of the polymerization solution is measured every 1 minute, and the time point when the temperature stops rising (the time point when the temperature no longer changes) corresponds to the maximum temperature.

[0127] The polymerization time is not particularly limited, but is preferably in the range of 1 second to 60 minutes, more preferably in the range of 10 seconds to 40 minutes, further preferably in the range of 15 seconds to 10 minutes, and most preferably in the range of 30 seconds to 3 minutes. If the polymerization time exceeds 60 minutes, the productivity and / or various physical properties of the obtained water-absorbing agent composition may be low. Here, the polymerization time refers to the time from when the polymerization start conditions are met (when a photodegradable polymerization initiator is used, it is when light irradiation starts; when a thermal decomposition polymerization initiator is used, it is when the polymerization initiator is added to the monomer aqueous solution) to when the maximum temperature is reached. That is, "polymerization time = (preparation time) + (time from the actual start of polymerization to when the maximum temperature is reached)".

[0128] Therefore, the time when the polymerization process starts refers to the time point when the polymerization start conditions are satisfied. The time when the polymerization process ends refers to the time point when the highest temperature is reached. The hydrogel is obtained at the time point when the polymerization ends. In addition, if it does not affect the effect of this embodiment, the hydrogel used is not limited to the time point when the polymerization ends, and the hydrogel at the stage before the polymerization ends (stage during polymerization) can also be used.

[0129] The increase rate of the solid content during polymerization is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more. In addition, the increase rate of the solid content can be determined by the difference between the solid content of the aqueous monomer solution and the solid content of the obtained hydrogel.

[0130] The solid content concentration of the water-containing gel obtained in the polymerization step is preferably in the range of 40 to 70% by mass, more preferably in the range of 45 to 55% by mass.

[0131] [Gel crushing process]

[0132] The hydrogel obtained in the polymerization step can be directly provided to the drying step. However, if the hydrogel is obtained by aqueous solution polymerization, for example, it is preferably subjected to gel grinding (chopping) using a grinder such as a gel grinder until the size of the hydrogel is about 1 / 10 or less, and then subjected to the drying step. In addition, when the hydrogel is subjected to gel grinding, a small amount of water or water vapor may be added as needed.

[0133] In the gel grinding step, the hydrogel obtained in the polymerization step is gel-ground until the mass average particle size d1 of the hydrogel converted to solid content is 1 mm or less, more preferably 800 μm or less, and even more preferably 500 μm or less. This allows the water-absorbing resin, polysaccharide and reducing agent to be uniformly kneaded, thereby achieving the effect of uniformly suppressing coloration of the entire water-absorbing agent composition.

[0134] Gel crushing is performed by various methods. As a method for gel crushing, specifically, for example, a method of extruding and crushing the gel using a screw-type extruder (meat grinder) with a die having an arbitrary porous structure can be cited. In addition, a plurality of machines can also be used in combination to implement gel crushing. For example, as a method for gel crushing that can be preferably used, the methods described in patent documents 14 to 17 (WO2011 / 126079, WO2016 / 158975, WO2016 / 204302, Japanese Patent Publication No. 2001-79829) and the like can be cited.

[0135] Therefore, the time when the gel grinding process starts refers to the time point when the hydrogel is put into a grinding machine such as a gel grinding machine, and before the gel grinding process starts (but after the polymerization process ends) refers to the period from the end of the polymerization process to the start of the gel grinding process. In addition, in the gel grinding process, it refers to the period from the start of the gel grinding process to the time before the gel is discharged from the grinding machine as a ground product.

[0136] The solid content concentration of the hydrogel obtained by pulverizing the gel (hereinafter referred to as "particulate hydrogel") is preferably in the range of 50 to 80% by mass, more preferably in the range of 55 to 70% by mass.

[0137] 〔Drying process〕

[0138] The granular hydrogel obtained by crushing the gel is dried to obtain a dried product. Examples of the drying method include heating drying, hot air drying, reduced pressure drying, infrared drying, microwave drying, drum drying, belt drying, azeotropic dehydration with a hydrophobic organic solvent, and high-humidity drying using high-temperature steam. Among these, hot air drying using a gas with a dew point of 40 to 100° C. (more preferably 50 to 90° C.) is more preferred.

[0139] The drying temperature is not particularly limited, but is preferably in the range of 100 to 200° C., more preferably in the range of 120 to 180° C., and further preferably in the range of 140 to 160° C. In the case of hot air drying, the hot air temperature is preferably in the range of 100 to 200° C., more preferably in the range of 120 to 180° C., and further preferably in the range of 140 to 160° C.

[0140] The drying time may be appropriately set without particular limitation, but is preferably in the range of about 10 seconds to 2 hours, more preferably in the range of about 1 minute to 1.5 hours, and still more preferably in the range of about 10 minutes to 1 hour.

[0141] The surface temperature of the particulate hydrogel before being placed in the dryer is preferably in the range of 40 to 110° C., more preferably in the range of 60 to 100° C. If the surface temperature is lower than 40° C., a spherical dried product may be produced during drying, and a large amount of fine powder may be produced during pulverization, resulting in lower physical properties of the water-absorbing agent composition.

[0142] In order to prevent the obtained water-absorbing agent composition from being colored, the waiting time before the particulate hydrogel after the gel pulverization step is put into the dryer is preferably short. The waiting time is preferably within 2 hours, more preferably within 1 hour, further preferably within 30 minutes, particularly preferably within 10 minutes, and most preferably within 2 minutes.

[0143] Therefore, the start of the drying step refers to the time point when the particulate hydrogel is put into the dryer.

[0144] In the drying step, the moisture content of the obtained dried product is preferably in the range of 3 to 15 mass %, more preferably in the range of 4 to 14 mass %, further preferably in the range of 5 to 13 mass %, and particularly preferably in the range of 6 to 12 mass %. If the moisture content of the dried product is less than 3 mass %, the various physical properties of the water absorbent composition may be low. If the moisture content of the dried product is higher than 15 mass %, the dried product may be difficult to pulverize in the pulverizing step.

[0145] 〔Crushing process〕

[0146] The dried product (water-absorbent resin or water-absorbent resin composition, hereinafter referred to as water-absorbent resin, etc.) obtained in the drying step may be pulverized as necessary to obtain particles having a size within a predetermined range. The pulverization method is not particularly limited, and examples thereof include methods using a vibration mill, a roll granulator, an elbow-type pulverizer, a roll mill, a high-speed rotary pulverizer (a pin mill, a hammer mill, a spiral mill, a roll mill), a drum mixer, and the like.

[0147] The shape of the pulverized water-absorbent resin or the like (pulverized product) may be any shape, such as granular, powdery, flake, or fibrous.

[0148] 〔Grading process〕

[0149] The pulverized product (water-absorbent resin, etc.) obtained in the pulverization step is classified as needed to select only particles (classified products) whose sizes fall within a specified range. The classification method is not particularly limited, and an example thereof is a screening method using a sieve. Specifically, for example, if a water-absorbent resin, etc. (classified product) with a size of 150 μm to 850 μm is to be obtained, the pulverized product can be first sieved with a sieve with a mesh of 850 μm, and the pulverized product that has passed the sieve can be sieved with a sieve with a mesh of 150 μm, and then the pulverized product that has not passed the sieve (remaining on the sieve) can be recovered.

[0150] The mass average particle size (D50) of the water-absorbing resin (classified product) before surface cross-linking is not particularly limited, but is preferably in the range of 250 μm to 450 μm, more preferably in the range of 275 μm to 425 μm, and further preferably in the range of 300 μm to 400 μm. In addition, the smaller the proportion of particles with a size less than 150 μm, the more preferred, usually preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 1% by mass or less. In addition, the proportion of particles with a size of 150 μm to 850 μm is preferably 95% by mass or more, more preferably 96% by mass or more, and further preferably 98% by mass or more (the upper limit is 100% by mass). The logarithmic standard deviation (σζ) of the particle size distribution is preferably in the range of 0.2 to 0.5, more preferably in the range of 0.25 to 0.45, and further preferably in the range of 0.30 to 0.40.

[0151] The particle size (mass average particle size, logarithmic standard deviation of particle size distribution, etc.) requirements of the water-absorbent resin etc. before surface crosslinking are preferably also applicable to the product after surface crosslinking, and further to the water-absorbent composition as the final product. Therefore, it is preferred that the water-absorbent resin etc. be surface crosslinked in such a way that the particle size before surface crosslinking is still maintained after surface crosslinking. It is particularly preferred that the water-absorbent resin etc. be surface crosslinked in such a way that the mass average particle size (D50) before surface crosslinking and the proportion of particles with a size of less than 150 μm are still maintained after surface crosslinking.

[0152] 〔Micro powder recovery process〕

[0153] The fine powder obtained in the classification process (for example, water-absorbent resin with a size of less than 150 μm) is recovered and regenerated as needed. The fine powder can be added to the monomer aqueous solution during the polymerization process, or it can be mixed with a large amount of water (especially water at a temperature of 50°C to the boiling point) (the mass ratio of fine powder to water is 5:4 to 3:7), and then added to the hydrogel obtained in the polymerization process. In this way, the amount of water-absorbent resin that cannot become the final product and needs to be discarded can be reduced.

[0154] 〔Surface cross-linking process〕

[0155] The water-absorbent resin etc. obtained through the above-mentioned steps before surface crosslinking is subjected to surface crosslinking to obtain a surface crosslinked water-absorbent resin etc. Surface crosslinking means forming a surface crosslinked layer having a higher crosslinking density than the inside on the surface of the water-absorbent resin etc. (near the surface: a depth of about several tens of micrometers from the surface of the water-absorbent resin etc.). Surface crosslinking can be performed, for example, by free radical crosslinking or surface polymerization at the particle surface, or by a surface crosslinking reaction using a surface crosslinking agent.

[0156] As the surface crosslinking agent, for example, oxazoline compounds, vinyl ether compounds, epoxy compounds, oxetane compounds, polyol compounds, polyamide polyamine epoxy halogen adducts, hydroxy acrylamide compounds, oxazolone compounds, bisoxazolone compounds or polyoxazolone compounds, 2-oxytetrahydro-1,3-oxazolidine compounds, alkylene carbonate compounds, polyvalent metal ions such as aluminum salts, etc. can be cited. These surface crosslinking agents are used alone or in combination. In addition, organic acids and / or inorganic acids can also be used together with the surface crosslinking agent. In addition, monomer polymerization can be performed on the surface of a water-absorbent resin to perform surface crosslinking.

[0157] As the surface crosslinking method, preferred are: a method using epoxy compounds and polyamide polyamine epoxy halogen adducts as surface crosslinking agents, a method using polyvalent metal ions such as aluminum salts, a method using organic acids and / or inorganic acids, and a method of polymerizing monomers on the surface of a water-absorbent resin, etc. These methods can promote the surface crosslinking reaction of the water-absorbent resin, etc. while maintaining the water content at low temperatures, thereby obtaining a water-absorbent composition having various excellent physical properties.

[0158] Specific examples of the surface crosslinking agent include: (di-, tri-, tetra-, poly)ethylene glycol, (di-, poly)propylene glycol, 1,3-propylene glycol, 2,2,4-trimethyl-1,3-pentanediol, (poly)glycerol, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, trimethylolpropane, di- or triethanolamine, pentaerythritol, sorbitol and other polyol compounds. Epoxy compounds such as (poly)ethylene glycol diglycidyl ether, (di-, poly)glycerol polyglycidyl ether, (di-, poly)propylene glycol diglycidyl ether, and glycidol; polyoxazoline compounds such as 1,2-ethylenebisoxazoline; alkylene carbonate compounds such as 1,3-dioxolane-2-one; polyvalent metal compounds such as aluminum sulfate, polyamide polyamine halopropylene oxide adducts (for example, Kymene 557LX, Kymene 557H, Kymene plus sold by Hercules, WS4002, WS4020, WS4010, WS4046 sold by Seikyo PMC Co., Ltd.); etc.

[0159] The amount of the surface crosslinking agent used is preferably 0.005 to 10 parts by mass, more preferably 0.005 to 5 parts by mass, and even more preferably 0.01 to 3 parts by mass relative to 100 parts by mass of the water-absorbing resin before surface crosslinking. If the amount of the surface crosslinking agent used is less than 0.005 parts by mass or exceeds 10 parts by mass, the various physical properties of the water-absorbing agent composition may be reduced.

[0160] As a solvent when mixing the water-absorbent resin and the surface crosslinking agent, water is preferably used. The amount of water used is preferably 1 to 10 parts by mass relative to 100 parts by mass of the water-absorbent resin before surface crosslinking. As a result, the surface crosslinking agent aqueous solution can fully penetrate the surface of the water-absorbent resin, etc., so that a multi-layer surface crosslinked layer with an appropriate thickness and crosslinking density can be formed.

[0161] In addition, a hydrophilic organic solvent may also be used as the solvent. Specifically, for example, the hydrophilic organic solvent includes lower alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, and tert-butanol; ketones such as acetone; ethers such as dioxane, tetrahydrofuran, and alkoxypolyethylene glycol; amides such as N,N-dimethylformamide; sulfoxides such as dimethyl sulfoxide; etc. The amount of the hydrophilic organic solvent used varies depending on the type and particle size of the water-absorbing resin, etc., but the amount of the hydrophilic organic solvent used is preferably 20 parts by mass or less, and more preferably in the range of 0.1 to 10 parts by mass, relative to 100 parts by mass of the water-absorbing resin, etc. before surface cross-linking.

[0162] The method of mixing the water-absorbing resin and the like with the surface crosslinking agent is not particularly limited, but a method of directly spraying or dropping the surface crosslinking agent dissolved in water and / or a hydrophilic organic solvent onto the water-absorbing resin and the like for mixing is preferred.

[0163] The mixing device used when mixing the water-absorbent resin and the surface crosslinking agent is preferably equipped with a large mixing force in order to mix the two uniformly and reliably. Specific examples of the mixing device include cylindrical mixers, double-walled cone mixers, V-shaped mixers, ribbon mixers, spiral mixers, flow-type rotating disk mixers, airflow mixers, double-arm kneaders, internal mixers, pulverizing kneaders, rotary mixers, spiral extruders, turbulent agitators, and the like.

[0164] After mixing the water-absorbent resin and the like with the surface crosslinking agent, the mixture may be heated as needed in order to promote the surface crosslinking reaction. The heating temperature is preferably in the range of 20 to 250°C, more preferably in the range of 30 to 200°C, and further preferably in the range of 50 to 170°C. According to one embodiment of the present invention, coloring can be suppressed, especially from the perspective of the surface crosslinking reaction above 100°C. The coloring of the water-absorbent composition (water-absorbent resin) caused by the surface crosslinking reaction of 100 to 250°C can be effectively suppressed. In addition, the heating time varies depending on the heating temperature, but is preferably in the range of 1 minute to 2 hours, more preferably in the range of 5 minutes to 1 hour, and further preferably in the range of 10 minutes to 30 minutes. As a preferred combination of heating temperature and heating time, for example, heating at 70 to 120°C for 3 minutes to 1 hour, heating at 100 to 250°C for 3 minutes to 1 hour, and heating at 130 to 170°C for 1 minute to 30 minutes can be cited. Through surface crosslinking, various physical properties such as the water absorption under pressure (AAP) of the water-absorbent resin are more superior.

[0165] Therefore, the completion of the surface cross-linking step means the time point when the predetermined heating time is completed.

[0166] In order to obtain a water-absorbing agent composition having excellent properties, it is preferred to carry out the surface crosslinking reaction while maintaining the water content of the water-absorbing resin etc. before surface crosslinking in the range of 3 to 15% by mass, more preferably 4 to 14% by mass, further preferably 5 to 13% by mass, and particularly preferably 6 to 12% by mass. If the water content of the water-absorbing resin etc. before surface crosslinking is less than 3% by mass, the various properties of the water-absorbing agent composition may be low. If the water content of the water-absorbing resin etc. before surface crosslinking is higher than 15% by mass, the handling properties (fluidity) of the water-absorbing agent composition may be low.

[0167] After surface crosslinking, the water-absorbing resin etc. may be further dried as needed. In addition, after surface crosslinking, water and additional additives may be added to the water-absorbing resin etc. as needed to adjust the moisture content and various physical properties. As the additional additives, for example, insoluble water particles such as hydrophilic amorphous silica, reducing agents, antibacterial agents, deodorants, chelating agents, polyvalent metal compounds, etc. may be cited. The amount of the additional additives used is preferably 0.001 to 20 parts by mass, more preferably 0.01 to 10 parts by mass, and further preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the water-absorbing resin etc. after surface crosslinking.

[0168] [Polysaccharide Addition Process]

[0169] The polysaccharide adding step is a step of adding a polysaccharide to at least one of the monomer aqueous solution, the hydrogel, the granular hydrogel, the dried product, the crushed product of the dried product and its classified product, the water-absorbing resin before the surface crosslinking, and the water-absorbing resin after the surface crosslinking during the period from the start of the polymerization step to the end of the surface crosslinking step. The polysaccharide is more preferably added after the end of the polymerization step, and is further preferably added at least one of the following stages: before the start of the gel crushing step (but after the end of the polymerization step), at the start of the gel crushing step, during the gel crushing step, and during the period from the crushing step to the start of drying. It is particularly preferred to add the polysaccharide at least one of the following stages: before the start of the gel crushing step (but after the end of the polymerization step), at the start of the gel crushing step, and during the gel crushing step.

[0170] The method of adding the polysaccharide is not particularly limited, and the entire amount of the polysaccharide may be added at once or in several portions. In addition, the polysaccharide is preferably added in a state such as granules or powder.

[0171] If the polysaccharide is added after the polymerization process is completed, the polysaccharide can be dispersed on the surface of the water-absorbent resin particles and exists at a high concentration on a part of the surface of the water-absorbent resin particles. By further uniformly mixing the water-absorbent resin and the polysaccharide, if the surface of the water-absorbent resin particles is compared to the sea and the polysaccharide is compared to the island, the water-absorbent resin and the polysaccharide exist in the form of islands. In addition, the polysaccharide exists at a high concentration on the surface of the water-absorbent resin particles. In other words, the content of the polysaccharide on the surface is higher than that in the interior of the water-absorbing agent composition. In addition, when the polysaccharide is added before the gel crushing process (but after the polymerization process is completed), at the beginning of the gel crushing process, and at least one stage in the gel crushing process, the method of adding the polysaccharide is not particularly limited, but in order to be able to mix more uniformly, the kneading method is more preferred. As a result, for example, when the polysaccharide is starch, even if the gelatinization process is not performed, the water contained in the water-absorbent resin can gelatinize (α-ize) the starch and integrate (composite) it with the water-absorbent resin. As a result, the reducing agent is uniformly dispersed in the composite resin formed by integrating the polysaccharide and the water-absorbing resin. Therefore, it is possible to suppress the "coloration caused by heating during the manufacturing process (mainly the process of surface cross-linking the water-absorbing resin composition (base polymer composition) after the drying process at high temperature)" that is present in conventional water-absorbing agent compositions containing polysaccharides.

[0172] The polysaccharide may be added in such a manner that the amount of polysaccharide in the water-absorbing agent composition reaches 10% by mass or more. The amount of polysaccharide added is 10% by mass or more relative to the total mass of the monomer composition and the polysaccharide used as raw materials in the polymerization step. The amount of polysaccharide contained in the water-absorbing agent composition is preferably 10% by mass or more, and more preferably 20% by mass or more, based on the total amount of the water-absorbing agent composition being 100% by mass. The upper limit of the amount of polysaccharide content is preferably 50% by mass or less, and more preferably 30% by mass or less.

[0173] In addition, if the polysaccharide is added after the water-absorbent resin polymerization step is completed, the polysaccharide can be dispersed on the surface of the water-absorbent resin and exists at a high concentration on a part of the surface of the water-absorbent resin. That is, the polysaccharide exists at a high concentration on the surface of the water-absorbent resin. In addition, when the polysaccharide is starch, it is easy to confirm whether the transparent water-absorbent resin and the polysaccharide colored by the iodine starch reaction exist in a phase-separated state by using iodine (performing an iodine starch reaction).

[0174] 〔Reducing agent adding process〕

[0175] The reducing agent adding step is a step of adding a reducing agent to at least one of the aqueous monomer solution, the hydrogel, the dried product, the pulverized product, or the water-absorbent resin during the period from the start of the polymerization step to the end of the surface crosslinking step. The reducing agent is more preferably added during the period from the end of the polymerization step to the start of the drying step (or the surface crosslinking step). More preferably, in the method for producing a water-absorbent resin composition according to one embodiment of the present invention, it is further preferred that a gel pulverizing step is further included between the polymerization step and the drying step, and the reducing agent is added during the period from the start of the gel pulverizing step (but after the end of the polymerization step) to the start of the surface crosslinking step. It is further preferred that the reducing agent is added at least one of the following stages: before the start of the gel pulverizing step (but after the end of the polymerization step), at the start of the gel pulverizing step, during the gel pulverizing step, and during the period from after the pulverizing step to the start of drying. It is particularly preferred that the reducing agent be added at least one of the following stages: before the start of the gel pulverizing step (but after the end of the polymerization step), at the start of the gel pulverizing step, and during the gel pulverizing step. It is most preferred that the reducing agent be added before the start of the gel pulverizing step (but after the end of the polymerization step) and / or at the start.

[0176] In addition, it is particularly preferred that both the polysaccharide and the reducing agent are added before the gel grinding step (but after the polymerization step) and / or at the beginning. In addition, in the method for producing a water-absorbent resin composition according to one embodiment of the present invention, in order to uniformly mix the polysaccharide and the reducing agent with the water-absorbent resin, a kneading step is preferably included. If the kneading step is included, for example, when the polysaccharide is starch, even if the gelatinization step is not performed, the water contained in the water-absorbent resin can gelatinize (alpha) the starch and integrate (composite) it with the water-absorbent resin, resulting in the reducing agent being uniformly dispersed in the composite resin formed by the integration of the polysaccharide and the water-absorbent resin. This form can suppress the "coloring caused by heating during the manufacturing process (mainly surface crosslinking at high temperature)" that exists in conventional water-absorbent compositions containing polysaccharides. The water-absorbent resin composition containing alpha-polysaccharides is particularly susceptible to coloring due to the heating step, but according to this embodiment, its coloring can be suppressed. The kneading step is preferably carried out during the gel grinding step and / or after the gel grinding step. In addition, the gel grinding step and the kneading step can be substantially the same step.

[0177] In addition, the solid content concentration of the mixture containing polysaccharides and hydrogel after kneading (but before the drying step) or after gel crushing is preferably in the range of 30 to 80% by mass, and more preferably in the range of 40 to 70% by mass. In other words, the water content in the mixture is preferably in the range of 20 to 70% by mass, and more preferably in the range of 30 to 60% by mass. The temperature of the mixture in the kneading step or the gel crushing step is preferably in the range of 50 to 100°C, more preferably in the range of 70 to 100°C, and further preferably in the range of 90 to 100°C.

[0178] The method of adding the reducing agent is not particularly limited, and the entire amount of the reducing agent may be added at once or in several portions. In order to more uniformly mix the reducing agent, it is preferred to add the reducing agent in a state dissolved in a solvent (preferably water).

[0179] The amount of the reducing agent added is adjusted so that the amount of the reducing agent contained in the water-absorbing agent composition is 10 ppm to 10,000 ppm relative to the total amount of the water-absorbing agent composition. The amount of the reducing agent added is 10 to 100,000 ppm relative to the total mass of the monomer composition and the polysaccharide used as raw materials for the polymerization step. The amount of the reducing agent added is more preferably 100 to 80,000 ppm, more preferably 1,000 to 50,000 ppm, and most preferably 5,000 to 30,000 ppm. In addition, the ratio between the amount of polysaccharide added and the amount of reducing agent added (the amount of polysaccharide added: the amount of reducing agent added) is preferably 99:1 to 80:20, more preferably 97:3 to 85:15, and more preferably 95:5 to 90:10.

[0180] By adding a reducing agent to the water-absorbing resin, coloration caused by heating during the production process of the water-absorbing agent composition can be prevented even if heat drying or surface crosslinking treatment under heating is performed during the production process. In addition, residual monomers contained in the water-absorbing agent composition at the final product shipment stage can be reduced.

[0181] [Differences from existing technologies]

[0182] As shown in Patent Documents 1 to 13, water-absorbent resins obtained by using polysaccharides as part or all of the water-absorbent resin raw materials are known, but the polysaccharides have low heat resistance, especially the polysaccharides mixed with hydrogels, which has the above-mentioned problems. The present inventors have conducted various studies to solve the above-mentioned problems and found that reducing agents can effectively prevent the polysaccharides (especially starch) mixed with water-absorbent resins (especially hydrogels) from coloring when heated at high temperatures, thereby completing the present invention.

[0183] In addition, conventionally, there are known technologies for adding a reducing agent to a water-absorbent resin in order to modify the water-absorbent resin (impart urine resistance to the water-absorbent resin (inhibit gel degradation caused by urine), reduce residual monomers in the water-absorbent resin, prevent coloration of the water-absorbent resin after long-term storage, etc.) (e.g., Patent Documents 17 to 21). However, these technologies do not suggest any effect as described above.

[0184] Furthermore, Patent Documents 1 to 13 concerning water-absorbent resins using polysaccharides do not suggest adding a reducing agent to the water-absorbent resins using polysaccharides, nor do they suggest that the reducing agent contributes to preventing the water-absorbent resins using polysaccharides from coloring when heated at high temperatures.

[0185] Furthermore, although the aforementioned Patent Documents 14 to 17 disclose gel pulverization of a hydrogel after polymerization, they also do not provide any suggestion of adding a reducing agent to a water-absorbent resin using a polysaccharide, or suggesting that a reducing agent contributes to preventing coloration of the water-absorbent resin using a polysaccharide when heated at a high temperature.

[0186] Even if the water absorbent composition of one embodiment of the present invention uses polysaccharides as at least a part of sustainable raw materials, the productivity is not reduced, and the heating (heat drying, surface crosslinking treatment under heating) during the manufacturing process does not cause coloring. The polyacrylic acid (salt)-based water-absorbing resin has a carboxylic acid (salt) group, and the resin is mixed with free carboxylic acids and alkaline compounds. Therefore, if polysaccharides such as starch are present, the heating during the manufacturing process is likely to cause coloring. In particular, in the process of surface crosslinking the water-absorbing resin composition (base polymer composition) after the drying process at a high temperature, the heating is more likely to cause coloring because the water content of the base polymer composition is low and the cooling effect is low. Therefore, it is difficult for the prior art to solve the problem of coloring. However, the water absorbent composition of one embodiment of the present invention and the method for manufacturing the water absorbent composition of one embodiment of the present invention can solve the problem of coloring that is difficult to solve in the prior art. The difference between the YI value of the obtained water absorbing agent composition (final product) and the YI value of the base polymer composition, i.e., ΔYI value (YI value of the water absorbing agent composition - YI value of the base polymer composition), is 20.0 or less, preferably 15.0 or less, more preferably 10.0 or less, and even more preferably 5.0 or less.

[0187] Furthermore, the water absorbing agent composition can be used even under high temperature conditions (heating conditions of 100° C. or higher).

[0188] [Various physical properties of water-absorbing agent composition]

[0189] The above-mentioned optional components may be added to the water absorbing agent composition obtained by performing the above-mentioned steps as needed.

[0190] The water absorbing agent composition obtained by performing the above steps has a yellowness index (YI value) of 60 or less, more preferably 50 or less, and even more preferably 40 or less (lower limit is 10) in accordance with ASTM D1925 due to coloring caused by heating during the production process of the water absorbing agent composition.

[0191] The residual monomer content in the water absorbing agent composition obtained by performing the above steps is 1000 ppm or less, more preferably 700 ppm or less, and even more preferably 500 ppm or less (the lower limit is 1 ppm).

[0192] In addition, the water absorbing agent composition obtained by performing the above steps has a water absorption under pressure (AAP0.3) of 10 g / g or more at 0.3 kPa, more preferably 12 g / g or more, and further preferably 15 g / g or more. The upper limit of the water absorption under pressure (AAP0.3) at 0.3 kPa is not particularly limited, but is 40 g / g or less, more preferably 35 g / g or less, and further preferably 30 g / g or less.

[0193] The water absorbing agent composition of one embodiment of the present invention obtained by performing the above steps can be preferably used in various water absorbing articles such as diapers, sanitary napkins, adult incontinence products (incontinence pads), pet sheets and other sanitary materials (sanitary products), agricultural and horticultural soil water retention agents, industrial water stop agents, etc.

[0194] (Example)

[0195] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not to be construed as being limited to these examples, and examples obtained by appropriately combining the technical means described in the examples are also included in the scope of the present invention.

[0196] <Evaluation Method>

[0197] 〔CRC (absorption ratio without pressure)〕

[0198] CRC (absorption capacity without pressure) is measured according to NWSP 241.0.R2 (15). Specifically, 0.2 g of the water-absorbing agent composition is placed in a non-woven bag, immersed in an excess of 0.9 mass % sodium chloride aqueous solution for 30 minutes, the water-absorbing agent composition is allowed to swell freely, and then dehydrated by a centrifuge (centrifugal force: 250 G), and CRC (absorption capacity without pressure) (unit: g / g) is measured.

[0199] 〔AAP (Absorption under pressure)〕

[0200] The AAP (absorption under pressure) was measured in accordance with NWSP 242.0.R2 (15), except that the pressure condition was changed from 0.7 psi to 0.3 psi. Specifically, 0.9 g of the water-absorbing agent composition was placed in an excess of 0.9 mass % sodium chloride aqueous solution at 2.07 kPa (21 g / cm 2 The mixture was allowed to swell under a pressure of 0.3 psi for 1 hour, and then the AAP (absorption under pressure) (unit: g / g) was measured. The result measured under a pressure of 0.3 psi was recorded as AAP0.3.

[0201] 〔Colorization〕

[0202] The coloring degree of the water-absorbing agent composition was measured using the Hunter Lab colorimeter. The measuring device used was a spectrocolorimeter (SE-7700) manufactured by Nippon Denshoku Industries Co., Ltd., and reflective measurement was selected as the measuring condition. The spectrocolorimeter was equipped with a container for powder / paste samples (inner diameter 30 mm, height 12 mm), a standard circular white plate No. 2 for powder / paste samples, and a 30Φ projection tube.

[0203] 5 g of the water absorbent composition is placed in the container for the powder / paste sample, and the L value, a value, b value, and YI value of the surface of the water absorbent composition are measured at room temperature (20-25°C) and a relative humidity of 50 RH%. The higher the L value, the brighter it is, and the smaller the YI value, the lower the coloring degree is and the closer it is to white. Using the same measuring device and the same measuring method, the object color, i.e., the a value and b value (chromaticity), which are other constant standards, can also be measured. The smaller the a value and b value, the lower the coloring degree is and the closer it is to white.

[0204] If the water absorbing agent composition is a water absorbing agent composition immediately after production or immediately before shipment (usually), or if it is a water absorbing agent composition stored within 1 year after production under storage conditions of an atmosphere of 30°C or lower and a relative humidity of 50%RH, it is determined that there is no change in color tone after the elapse of time, and the color tone is taken as the coloration degree of the water absorbing agent composition.

[0205] 〔Residual monomer〕

[0206] 1.0 g of the water absorbing agent composition was added to 200 ml of a 0.9 mass % sodium chloride aqueous solution and stirred for 1 hour to extract the residual monomers. The amount of the residual monomers extracted in the sodium chloride aqueous solution (unit: ppm (mass standard)) was then measured and quantified using a high performance liquid chromatograph.

[0207] 〔Content of sodium sulfite〕

[0208] The sodium sulfite content of the water absorbing agent composition was determined by extracting a soluble component from the water absorbing agent composition and then measuring and quantifying the extracted soluble component (unit: ppm (mass basis)) using a high performance liquid chromatograph. Specifically, the quantification was performed by the following method.

[0209] In addition, in Examples and Comparative Examples, the content of sodium sulfite corresponds to the amount of the reducing agent contained in the water absorbing agent composition.

[0210] [Extraction of soluble components]

[0211] 0.1 g of the water absorbing agent composition was added to 100 g of a 0.1% by mass formaldehyde aqueous solution, and the mixture was stirred at 500 rpm for 1 hour. The supernatant of the obtained aqueous solution was filtered with qualitative filter paper (No. 2 manufactured by ADVANTEC) to obtain an extract solution.

[0212] [Quantitative analysis using high performance liquid chromatography]

[0213] Regarding the high performance liquid chromatograph for quantitatively measuring the sodium sulfite content, the following configuration can be cited, for example.

[0214] Ion Chromatography System: Dionex Integrion RFIC System

[0215] Column: Dionex IonPac AS11-HC, Dionex IonPac AG11-HC

[0216] First, sodium sulfite as a quantitative object is dissolved in a 0.1% by mass formaldehyde aqueous solution to prepare an aqueous sodium sulfite solution of an optional concentration. The aqueous solution is analyzed using a high performance liquid chromatograph having the above-mentioned structure, and a reference detection line is prepared based on the relationship between the peak area of ​​the obtained chromatogram and the concentration of sodium sulfite. The peak detected by the high performance liquid chromatograph is the corresponding peak of the sulfite ion generated by the ionization of sodium sulfite, so when calculating, the sulfite ions are all regarded as sodium sulfite for mass conversion.

[0217] Next, the extract solution to be measured was analyzed using the high performance liquid chromatograph having the above-mentioned configuration, and the content of sodium sulfite in the water absorbing agent composition was calculated based on the relationship between the peak area of ​​the obtained chromatogram and the reference detection line.

[0218] In addition, unless otherwise specified, the raw material compounds, reaction reagents, and solvents used in Examples and Comparative Examples are all commercially available products (for example, commercial products sold by Nippon Shokubai Co., Ltd.).

[0219] [Example 1]

[0220] (Preparation step of polymerization solution (monomer aqueous solution))

[0221] In a 2 L polypropylene container, 416.5 g of acrylic acid, 6.13 g of a 10% by mass polyethylene glycol diacrylate (molecular weight: 523) acrylic acid solution as an internal crosslinking agent (0.02 mol % relative to acrylic acid), 1.29 g of a 2.0% by mass diethylenetriamine pentaacetic acid·trisodium (DTPA·3Na) aqueous solution as a chelating agent (0.96 mmol % relative to acrylic acid), 352.6 g of a 48.5% by mass sodium hydroxide aqueous solution, and 405.1 g of deionized water (ion exchange water) were uniformly mixed to prepare a monomer aqueous solution.

[0222] (Production of water-absorbent resin composition)

[0223] At a liquid temperature of 77.5°C, while stirring the aqueous monomer solution, 18.4 g of a 4.5% by mass sodium persulfate aqueous solution as a polymerization initiator was added. Then, the aqueous monomer solution was injected into a stainless steel cylinder-type container whose temperature was adjusted to 50°C by a hot plate. After 3 minutes after the start of the polymerization reaction, the hydrogel was taken out and cut into pieces of 60±5 g each. Then, the entire amount of the cut gel was placed in a plastic bag (OK bag No. 18 manufactured by Okura Industries Co., Ltd.), and then 76.7 g of a 10% by mass sodium sulfite aqueous solution as a reducing agent was added thereto (18750 ppm relative to the solid content in the hydrogel, 15000 ppm relative to the total mass of the monomer composition and the polysaccharide). The mouth of the plastic bag was immediately tied and shaken until no water droplets adhered to the plastic bag.

[0224] The hydrogel obtained by the above operation was added to a meat grinder (manufactured by Hiraga Manufacturing Co., Ltd.: Model 32; die hole diameter: 6.4 mm) at intervals of 6 seconds, and at the same time, deionized water heated to 90°C was added at an input rate of 29 g per minute to grind the hydrogel, thereby obtaining a granular hydrogel.

[0225] 787.0 g of the granular hydrogel and 97.0 g of tapioca starch acetate BK-V (manufactured by Tokai Starch Co., Ltd.) as a polysaccharide (solid content 90%. The amount added is 20% by mass relative to the solid content in the hydrogel and the total mass of the monomer composition and the polysaccharide. The content is 20% by mass relative to the water-absorbing agent composition) were placed in a plastic bag (manufactured by Okura Industries: OK bag No. 15), the mouth of the plastic bag was immediately tied, and then shaken until the whole was uniform. Thus, a mixture was obtained.

[0226] The obtained mixture was put into a 2.5L small kneading machine (manufactured by Koike Iron Works Co., Ltd.) with a temperature adjustment of 90°C, and kneading and crushing were started. The kneading speed was set to 6 speeds by a transmission, and then 116.0 g of deionized water (ion exchange water) was added to the kneaded product. Then, the kneading machine was covered with a lid and kneaded for 15 minutes to obtain a starch kneading gel.

[0227] 700.0 g of the starch kneaded gel was spread on a 50-mesh metal net and dried with hot air at 170°C for 45 minutes. The dried product was crushed with a roll mill (Inoguchi Giken Co., Ltd.: WML type roll mill) and further sieved with JIS sieves with mesh sizes of 600 μm and 300 μm. Thus, a water-absorbent resin composition (base polymer composition) with a random crushed particle size of 300 to 600 μm was obtained. The residual sodium sulfite, L value, a value, b value and YI value of the obtained base polymer composition were measured, and the results are recorded in Table 2.

[0228] A surface crosslinking agent solution consisting of 0.75 parts by mass of propylene glycol, 0.07 parts by mass of DENACOL EX-810 (manufactured by Nagase ChemteX Co., Ltd.), and 1.75 parts by mass of deionized water (ion exchange water) was added to 100 parts by mass of the obtained base polymer composition, and the mixture was uniformly mixed to obtain a mixture. The mixture was then heated at 100° C. for 40 minutes to perform a surface crosslinking treatment.

[0229] The surface-crosslinked water-absorbing resin composition was pulverized so as to pass through a JIS standard sieve having an opening of 850 μm, thereby obtaining a surface-crosslinked water-absorbing agent composition.

[0230] The CRC, AAP0.3, residual monomers, residual sodium sulfite, L value, a value, b value and YI value of the obtained water absorbing agent composition were measured, and the results are shown in Table 1. In addition, the difference between the YI value of the obtained water absorbing agent composition and the YI value of the base polymer composition, that is, the ΔYI value (YI value of the water absorbing agent composition - YI value of the base polymer composition) was calculated and shown in Table 2.

[0231] [Example 2]

[0232] In addition to Example 1, the surface crosslinking agent solution was changed to a solution obtained by uniformly mixing 0.4 parts by mass of ethylene carbonate, 0.7 parts by mass of propylene glycol, and 2.9 parts by mass of deionized water (ion exchange water) with respect to 100 parts by mass of the base polymer resin composition (base polymer composition), and the heating treatment was changed to 210° C., and the same operation as in Example 1 was carried out to obtain a surface crosslinked water absorbent composition.

[0233] The CRC, AAP0.3, residual monomers, residual sodium sulfite, L value, a value, b value and YI value of the obtained water absorbing agent composition were measured, and the results are shown in Table 1. In addition, the difference between the YI value of the water absorbing agent composition and the YI value of the base polymer composition, that is, the ΔYI value (YI value of the water absorbing agent composition - YI value of the base polymer composition) was calculated and shown in Table 2.

[0234] [Example 3]

[0235] A water-absorbent resin composition (base polymer composition) was obtained in the same manner as in Example 2 except that the 10% by mass sodium sulfite aqueous solution was not added to the hydrogel.

[0236] With respect to 100 parts by mass of the obtained base polymer composition, 5 parts by mass of a 20% by mass sodium sulfite aqueous solution (10,000 ppm relative to the total mass of the monomer composition and the polysaccharide) were uniformly mixed, and heated at 60°C for 30 minutes to obtain a base polymer composition containing sodium sulfite. The residual sodium sulfite, L value, a value, b value and YI value of the obtained base polymer composition containing sodium sulfite were measured, and the results are recorded in Table 2. Next, the base polymer containing sodium sulfite was subjected to surface crosslinking in the same manner as in Example 2 to obtain a surface crosslinked water absorbent composition. The CRC, AAP0.3, residual monomer, residual sodium sulfite, L value, a value, b value and YI value of the obtained water absorbent composition were measured, and the results are recorded in Table 1. In addition, the difference between the YI value of the obtained water absorbent composition and the YI value of the base polymer composition, that is, the ΔYI value (YI value of the water absorbent composition - YI value of the base polymer composition) was calculated and recorded in Table 2.

[0237] [Comparative Example 1]

[0238] A water absorbing agent composition was obtained in the same manner as in Example 1 except that the 10 mass % sodium sulfite aqueous solution and tapioca starch acetate BK-V were not added to the water-containing gel.

[0239] However, when kneading with a small kneader, the water content of the mixture put into the small kneader was adjusted to be the same as the water content of the mixture in Example 1. That is, without mixing the hydrogel with the 10 mass % sodium sulfite aqueous solution, one of the cut hydrogels was put into the meat grinder every 6 seconds, and at the same time, 50 g of deionized water heated to 90° C. was put into the meat grinder every minute to grind the hydrogel, thereby obtaining a granular hydrogel. Furthermore, without mixing the granular hydrogel with tapioca starch acetate BK-V, 984 g of the granular hydrogel and 16 g of deionized water were put into the small kneader and kneaded.

[0240] The residual sodium sulfite, L value, a value, b value, and YI value of the obtained base polymer composition were measured. The results are shown in Table 2.

[0241] The CRC, AAP0.3, residual monomers, residual sodium sulfite, L value, a value, b value and YI value of the obtained water absorbing agent composition were measured, and the results are shown in Table 1. In addition, the difference between the YI value of the water absorbing agent composition and the YI value of the base polymer composition, that is, the ΔYI value (YI value of the water absorbing agent composition - YI value of the base polymer composition) was calculated and shown in Table 2.

[0242] [Comparative Example 2]

[0243] A water absorbing agent composition was obtained in the same manner as in Example 2 except that the 10 mass % sodium sulfite aqueous solution was not added to the hydrogel.

[0244] Specifically, the cut gel was not mixed with the 10 mass % sodium sulfite aqueous solution, and one cut gel was added to the meat grinder every 6 seconds, and deionized water heated to 90° C. was added and pulverized to obtain a granular hydrogel. However, instead of using the input amount of 29 g per minute in Example 2, the deionized water heated to 90° C. was input at an input amount of 50 g per minute.

[0245] The residual sodium sulfite, L value, a value, b value and YI value of the obtained base polymer composition were measured. The results are recorded in Table 2. The CRC, AAP0.3, residual monomers, residual sodium sulfite, L value, a value, b value and YI value of the obtained water absorbing agent composition were measured, and the results are recorded in Table 1. In addition, the difference between the YI value of the obtained water absorbing agent composition and the YI value of the base polymer composition, that is, the ΔYI value (YI value of the water absorbing agent composition-YI value of the base polymer composition) was calculated and recorded in Table 2.

[0246] (Table 1)

[0247]

[0248] (Table 2)

[0249]

[0250] As can be seen from Table 1, the water-absorbing agent composition of Example 1 obtained by adding a polysaccharide (tapioca starch acetate) to a water-absorbing resin (particulate hydrogel) has a YI value that is substantially the same as that of the water-absorbing agent composition of Comparative Example 1 that does not contain a polysaccharide. In addition, the water-absorbing agent compositions of Examples 2 and 3 (final products after surface crosslinking) have lower YI values ​​than that of the water-absorbing agent composition of Comparative Example 2 (final product after surface crosslinking). That is, it can be seen that the coloring of the water-absorbing agent compositions of Examples 1 to 3 containing a polysaccharide is suppressed.

[0251] In addition, the water-absorbent resin compositions of Examples 2 and 3 have a smaller increase in YI value (ΔYI value) relative to the base polymer composition (intermediate product) before surface crosslinking than the water-absorbent resin composition of Comparative Example 2. This is also true for Example 1. This shows that the addition of a reducing agent can effectively prevent coloring during high-temperature heating (hot air drying and surface crosslinking treatment) during the production process.

[0252] According to the present invention, by adding a reducing agent in a specific step during the production of a water-absorbent resin containing a polysaccharide, the water-absorbent resin can be produced under the same conditions as conventional water-absorbent resins, and there is no need to invest in new equipment or lower the drying temperature to prevent coloration, thereby obtaining a water-absorbent resin with high productivity and high physical properties.

[0253] (Industrial Applicability)

[0254] The water absorbing agent composition of one embodiment of the present invention can be preferably used in various water absorbing articles such as diapers, sanitary napkins, adult incontinence products (incontinence pads), pet sheets and other sanitary materials (sanitary products), agricultural and horticultural soil water retention agents, industrial water stop agents, etc.

Claims

1. A method for producing a water-absorbing agent composition, wherein: The water-absorbing agent composition contains polyacrylic acid and / or polyacrylic acid salt-based water-absorbing resin, polysaccharides and a reducing agent. The manufacturing method is characterized by: The steps for producing the water absorbing agent composition include a polymerization step, a gel grinding step, a drying step, and a surface crosslinking step of surface crosslinking the dried base polymer composition. adding the polysaccharide after the polymerization step is completed and before the gel grinding step is started, at the start of the gel grinding step, or in at least one stage of the gel grinding step; Furthermore, the reducing agent is added during the period from before the gel pulverization step after the polymerization step to before the surface cross-linking step. At any stage during the period from the end of the polymerization step to the end of the surface cross-linking step, adding: 10% by mass or more of the polysaccharide and 10 ppm to 100,000 ppm of the reducing agent relative to the total mass of the monomer composition introduced into the polymerization step and the polysaccharide added in a step after the end of the polymerization step, The difference between the YI value of the water absorbing agent composition and the YI value of the base polymer composition, that is, the ΔYI value, is 15.0 or less.

2. The method for producing a water absorbing agent composition according to claim 1, wherein: The surface cross-linking process includes a surface cross-linking reaction at 100 to 250°C.

3. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the polysaccharide contained in the water absorbing agent composition is 10% by mass or more, based on 100% by mass of the total amount of the water absorbing agent composition.

4. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the polysaccharide contained in the water absorbing agent composition is 20% by mass or more, based on 100% by mass of the total amount of the water absorbing agent composition.

5. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the polysaccharide contained in the water absorbing agent composition is 50% by mass or less, based on 100% by mass of the total amount of the water absorbing agent composition.

6. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the polysaccharide contained in the water absorbing agent composition is 30% by mass or less, based on 100% by mass of the total amount of the water absorbing agent composition.

7. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the reducing agent added is 100 to 80,000 ppm based on the total mass of the monomer composition and the polysaccharide used as raw materials in the polymerization step.

8. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the reducing agent added is 1,000 to 50,000 ppm relative to the total mass of the monomer composition and the polysaccharide used as raw materials in the polymerization step.

9. The method for producing a water absorbing agent composition according to claim 1, wherein: The amount of the reducing agent added is 5000 to 30000 ppm based on the total mass of the monomer composition and the polysaccharide used as raw materials in the polymerization step.

10. The method for producing a water absorbing agent composition according to claim 1, wherein: The ratio between the amount of the polysaccharide added and the amount of the reducing agent added, that is, the amount of the polysaccharide added: the amount of the reducing agent added is 99:1 to 80:

20.

11. The method for producing a water absorbing agent composition according to claim 1, wherein: The ratio between the amount of the polysaccharide added and the amount of the reducing agent added, that is, the amount of the polysaccharide added: the amount of the reducing agent added is 97:3 to 85:

15.

12. The method for producing a water absorbing agent composition according to claim 1, wherein: The ratio between the amount of the polysaccharide added and the amount of the reducing agent added, that is, the amount of the polysaccharide added: the amount of the reducing agent added is 95:5 to 90:

10.

13. The method for producing a water absorbing agent composition according to claim 1, wherein: The reducing agent contains one or more selected from the group consisting of an inorganic compound containing a sulfur atom, an organic compound containing a sulfur atom, and an inorganic compound containing a phosphorus atom.

14. The method for producing a water absorbing agent composition according to claim 1, wherein: The reducing agent is a reducing agent containing an inorganic compound containing a sulfur atom.

15. The method for producing a water absorbing agent composition according to claim 1, wherein: The reducing agent is sodium bisulfite and / or sodium sulfite.

16. The method for producing a water absorbing agent composition according to claim 13, wherein: The sulfur atom-containing inorganic compound includes one or more selected from the group consisting of sulfites, hydrogensulfites, ferrous salts, and cuprous salts.

17. The method for producing a water absorbing agent composition according to claim 16, wherein: The sulfite contains one or more selected from the group consisting of sodium sulfite, potassium sulfite, and ammonium sulfite.

18. The method for producing a water absorbing agent composition according to claim 16, wherein: The bisulfite contains one or more selected from the group consisting of sodium bisulfite, potassium bisulfite, and ammonium bisulfite.

19. The method for producing a water absorbing agent composition according to claim 16, wherein: The ferrous salt comprises ferrous sulfate.

20. The method for producing a water absorbing agent composition according to claim 16, wherein: The cuprous salt comprises cuprous sulfate.

21. The method for producing a water absorbing agent composition according to claim 1, wherein: The reducing agent is a reducing agent containing an organic compound containing a sulfur atom.

22. The method for producing a water absorbing agent composition according to claim 21, wherein: The sulfur atom-containing organic compound includes one or more selected from the group consisting of 2-hydroxy-2-sulfonic acid acetic acid and its salts and 2-hydroxy-2-sulfinic acid acetic acid and its salts.

23. The method for producing a water absorbing agent composition according to claim 1, wherein: The reducing agent is a reducing agent containing an inorganic compound containing a phosphorus atom.

24. The method for producing a water absorbing agent composition according to claim 23, wherein: The phosphorus atom-containing inorganic compound includes at least one selected from the group consisting of phosphorous acid and phosphite salts, hydrogen phosphite salts, hypophosphorous acid and hypophosphite salts.

25. The method for producing a water absorbing agent composition according to claim 24, wherein: The phosphorous acid and phosphite contain at least one selected from the group consisting of disodium phosphite, dipotassium phosphite, and diammonium phosphite.

26. The method for producing a water absorbing agent composition according to claim 24, wherein: The hydrogen phosphite contains one or more selected from the group consisting of sodium hydrogen phosphite, potassium hydrogen phosphite, and ammonium hydrogen phosphite.

27. The method for producing a water absorbing agent composition according to claim 24, wherein: The hypophosphorous acid and the hypophosphite contain one or more selected from the group consisting of sodium hypophosphite, potassium hypophosphite, and ammonium hypophosphite.

28. The method for producing a water absorbing agent composition according to claim 1, wherein: The polysaccharides are natural polysaccharides obtained from organisms or modified products thereof.

29. The method for producing a water absorbing agent composition according to claim 1, wherein: The polysaccharide is selected from the following polysaccharides: starch, amylopectin, amylose, cellulose, galactomannan, glucomannan, xanthan gum, carrageenan, chitin, chitosan, and modified substances thereof.

30. The method for producing a water absorbing agent composition according to claim 29, wherein: The polysaccharide is starch and / or modified starch.

31. The method for producing a water absorbing agent composition according to claim 29, wherein: The starch is selected from the following starches: corn starch, potato starch, wheat starch, tapioca starch, waxy corn starch, rice starch, and sweet potato starch.

32. The method for producing a water absorbing agent composition according to claim 29, wherein: The cellulose is a cellulose selected from the group consisting of cotton, wood-derived pulp, bacterial cellulose, lignocellulose, regenerated cellulose, and microcrystalline cellulose.

33. The method for producing a water absorbing agent composition according to claim 29, wherein: The galactomannan is a galactomannan selected from the group consisting of guar gum, locust bean gum, tara gum, and cassia gum.

34. The method for producing a water absorbing agent composition according to claim 1, wherein: The particle size of the polysaccharide is in the range of 1 μm to 1000 μm.

35. The method for producing a water absorbing agent composition according to claim 1, wherein: The particle size of the polysaccharide is in the range of 1 μm to 500 μm.

36. The method for producing a water absorbing agent composition according to claim 1, wherein: The particle size of the polysaccharide is in the range of 1 μm to 200 μm.

37. The method for producing a water absorbing agent composition according to claim 29, wherein: The particle size of the starch is in the range of 1 μm to 150 μm.

38. The method for producing a water absorbing agent composition according to claim 29, wherein: The particle size of the starch is in the range of 1 μm to 100 μm.

39. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 500 or more.

40. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 1000 or more.

41. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 2000 or more.

42. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 5000 or more.

43. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is greater than 10,000.

44. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 10 million or less.

45. The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 8 million or less.

46. ​​The method for producing a water absorbing agent composition according to claim 1, wherein: The molecular weight of the polysaccharide is 5 million or less.

47. A water-absorbing agent composition comprising a polyacrylic acid and / or polyacrylic acid salt-based water-absorbing resin, a polysaccharide and a reducing agent, characterized in that: The water absorbing agent composition is produced by the method for producing a water absorbing agent composition according to any one of claims 1 to 46, wherein: The water absorbing agent composition is surface cross-linked. The water absorbing agent composition contains 10 mass % or more of the polysaccharide and 10 ppm to 10000 ppm of the reducing agent, The water absorbing agent composition has a YI value indicating a degree of coloration of 60 or less, The residual monomer content of the water absorbing agent composition is 1000 ppm or less.

48. The water absorbing agent composition according to claim 47, characterized in that The reducing agent contains one or more selected from the following: Inorganic compounds containing sulfur atoms, organic compounds containing sulfur atoms, and inorganic compounds containing phosphorus atoms.

49. The water absorbing agent composition according to claim 47, characterized in that The reducing agent is a reducing agent containing an inorganic compound containing a sulfur atom.

50. The water absorbing agent composition according to claim 47, characterized in that The reducing agent is sodium bisulfite and / or sodium sulfite.

51. The water absorbing agent composition according to claim 48, characterized in that The sulfur atom-containing inorganic compound includes one or more selected from the group consisting of sulfites, hydrogensulfites, ferrous salts, and cuprous salts.

52. The water absorbing agent composition according to claim 51, characterized in that The sulfite contains one or more selected from the group consisting of sodium sulfite, potassium sulfite, and ammonium sulfite.

53. The water absorbing agent composition according to claim 51, characterized in that The bisulfite contains one or more selected from the group consisting of sodium bisulfite, potassium bisulfite, and ammonium bisulfite.

54. The water absorbing agent composition according to claim 51, characterized in that The ferrous salt comprises ferrous sulfate.

55. The water absorbing agent composition according to claim 51, characterized in that The cuprous salt comprises cuprous sulfate.

56. The water absorbing agent composition according to claim 47, characterized in that The reducing agent is a reducing agent containing an organic compound containing a sulfur atom.

57. The water absorbing agent composition according to claim 56, characterized in that The sulfur atom-containing organic compound includes one or more selected from the group consisting of 2-hydroxy-2-sulfonic acid acetic acid and its salts and 2-hydroxy-2-sulfinic acid acetic acid and its salts.

58. The water absorbing agent composition according to claim 47, characterized in that The reducing agent is a reducing agent containing an inorganic compound containing a phosphorus atom.

59. The water absorbing agent composition according to claim 58, characterized in that The phosphorus atom-containing inorganic compound includes at least one selected from the group consisting of phosphorous acid and phosphite salts, hydrogen phosphite salts, hypophosphorous acid and hypophosphite salts.

60. The water absorbing agent composition according to claim 59, characterized in that The phosphorous acid and phosphite contain at least one selected from the group consisting of disodium phosphite, dipotassium phosphite, and diammonium phosphite.

61. The water absorbing agent composition according to claim 59, characterized in that The hydrogen phosphite contains one or more selected from the group consisting of sodium hydrogen phosphite, potassium hydrogen phosphite, and ammonium hydrogen phosphite.

62. The water absorbing agent composition according to claim 59, characterized in that The hypophosphorous acid and the hypophosphite contain one or more selected from the group consisting of sodium hypophosphite, potassium hypophosphite, and ammonium hypophosphite.

63. The water absorbing agent composition according to claim 47, characterized in that The amount of the reducing agent is in the range of 30 to 5000 ppm relative to the total amount of the water absorbing agent composition.

64. The water absorbing agent composition according to claim 47, characterized in that The amount of the reducing agent is in the range of 50 to 3000 ppm based on the total amount of the water absorbing agent composition.

65. The water absorbing agent composition according to claim 47, characterized in that The polysaccharides are natural polysaccharides obtained from organisms or modified products thereof.

66. The water absorbing agent composition according to claim 47, characterized in that The polysaccharide is selected from the following polysaccharides: starch, amylopectin, amylose, cellulose, galactomannan, glucomannan, xanthan gum, carrageenan, chitin, chitosan, and modified substances thereof.

67. The water absorbing agent composition according to claim 66, characterized in that The polysaccharide is starch and / or modified starch.

68. The water absorbing agent composition according to claim 66, characterized in that The starch is selected from the following starches: corn starch, potato starch, wheat starch, tapioca starch, waxy corn starch, rice starch, and sweet potato starch.

69. The water absorbing agent composition according to claim 66, characterized in that The cellulose is a cellulose selected from the group consisting of cotton, wood-derived pulp, bacterial cellulose, lignocellulose, regenerated cellulose, and microcrystalline cellulose.

70. The water absorbing agent composition according to claim 66, characterized in that The galactomannan is a galactomannan selected from the group consisting of guar gum, locust bean gum, tara gum, and cassia gum.

71. The water absorbing agent composition according to claim 47, characterized in that The particle size of the polysaccharide is in the range of 1 μm to 1000 μm.

72. The water absorbing agent composition according to claim 47, characterized in that The particle size of the polysaccharide is in the range of 1 μm to 500 μm.

73. The water absorbing agent composition according to claim 47, characterized in that The particle size of the polysaccharide is in the range of 1 μm to 200 μm.

74. The water absorbing agent composition according to claim 66, characterized in that The particle size of the starch is in the range of 1 μm to 150 μm.

75. The water absorbing agent composition according to claim 66, characterized in that The particle size of the starch is in the range of 1 μm to 100 μm.

76. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 500 or more.

77. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 1000 or more.

78. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 2000 or more.

79. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 5000 or more.

80. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is greater than 10,000.

81. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 10 million or less.

82. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 8 million or less.

83. The water absorbing agent composition according to claim 47, characterized in that The molecular weight of the polysaccharide is 5 million or less.

84. The water absorbing agent composition according to claim 47, characterized in that The amount of the polysaccharide is 20% by mass or more based on 100% by mass of the total amount of the water absorbing agent composition.

85. The water absorbing agent composition according to claim 47, characterized in that The amount of the polysaccharide is 50% by mass or less based on 100% by mass of the total amount of the water absorbing agent composition.

86. The water absorbing agent composition according to claim 47, characterized in that The amount of the polysaccharide is 30% by mass or less based on 100% by mass of the total amount of the water absorbing agent composition.

87. The water absorbing agent composition according to claim 47, characterized in that The residual monomer content of the water absorbing agent composition is 700 ppm or less.

88. The water absorbing agent composition according to claim 47, characterized in that The residual monomer content of the water absorbing agent composition is 500 ppm or less.

89. The water absorbing agent composition according to claim 47, characterized in that The lower limit of the residual monomers in the water absorbing agent composition is 1 ppm.

90. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorbency under pressure AAP0.3 of 10 g / g or more under a pressure of 0.3 kPa.

91. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorbency under pressure AAP0.3 of 12 g / g or more under a pressure of 0.3 kPa.

92. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorbency under pressure AAP0.3 of 15 g / g or more under a pressure of 0.3 kPa.

93. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorbency under pressure AAP0.3 of 40 g / g or less under a pressure of 0.3 kPa.

94. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorbency under pressure AAP0.3 of 35 g / g or less under a pressure of 0.3 kPa.

95. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has an absorption under pressure AAP0.3 of 30 g / g or less under a pressure of 0.3 kPa.

96. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has a yellowness index (YI) value of 50 or less based on ASTM D1925.

97. The water absorbing agent composition according to claim 47, characterized in that The water absorbing agent composition has a yellowness index (YI) value of 40 or less based on ASTM D1925.

98. The water absorbing agent composition according to claim 47, characterized in that The lower limit of the yellowness index, ie, the YI value, of the water absorbing agent composition according to ASTM D1925 is 10.

99. A water absorbing agent composition, The water absorbing agent composition is produced by the method for producing a water absorbing agent composition according to any one of claims 1 to 46.

Citation Information

Patent Citations

  • Production of water absorbing resin

    JP1979053165A

  • Water-absorptive composition

    JP1988118375A

  • Production of water-swellable polymer

    JP1989062317A

  • Water absorbing resin and its preparation

    JP2001079829A

  • Manufacturing method of water-absorbable resin

    JP2003206305A